Nutritive Value and the Quality of Ensiled Napier Grass (Pennisetum purpureum Schum.) and Banana (Musa acuminata) Peelings - Randa, Sangle Y; Lekitoo, Marlyn N; Iyai, Deny A; Pattiselanno, Freddy (ANIMAL PRODUCTION, 2017)
This paper aimed to evaluate the nutritive value and the quality of ensiled Napier grass (Pennisetum purpureum Schum) and banana (Musa acuminate) peelings.  Different levels of banana peeling and Napier grass were used in this study.  The levels of Napier grass and banana peeling compared as treatments with four replications were as follows: 100% Napier Grass (NG), 75% (NG) + 25% Banana Peeling (BP), 50%NG + 50%BP, 25%NG + 75% BP and 100%BP. Napier grass and banana peeling were mixed based on the percentage combination as treatments, weighed and placed into empty jam bottle with weights ranging from 64.4 grams to 509.2 grams as a simulated laboratory silo. Samples were stored in eight weeks at the Dairy Training Research Institute. Proximate analyses were done at Animal Nutrition Laboratory Institute of Animal Science while ADF, NDF, IVDMD, and IVOMD were done at the Animal Nutrition Division Laboratory at Dairy Training and Research Institute, UP Los Baños. Physically, the color of silage were light yellow with a  little greenish color for 100% napier grass, light to moderately yellow for the  three combinations of napier and banana peel and  yellow for 100% banana peel. Texture ranged from dry and coarse for napier grass, relatively dry for the combinations and moderately wet for the banana peel. The napier grass had a slightly acidic smell, the combinations had slightly sweet, acidic smell while the 100% banana peel had a sweeter, acidic smell.  Likewise, pH before ensiling had ranged from 5.7 (25%NG + 75%BP) to 7.5 ( 100% BP) while after  ensiling the pH changed from 4.575  ( 100% napier grass) to 5.75 ( 100% banana peel ). There were significant differences on DM, Moisture, CP, EE, CF, and Ash before ensiling. Similar trend was observed after ensiling except the ash content of all the treatments. ADF and NDF did not show significant variations in all treatments. IVDMD and IVOMD before ensiling varied significantly, but after ensiling only IVDMD of the treatments differed significantly. In terms of physical attributes, nutritive value and digestibility, banana peel can be used as silage material. All treatments generated comparable acceptability when fed to the animal.  It is suggested that further study, specifically in vivo trial, will be conducted to validate the feeding and nutritional value of banana peel as alternative silage for ruminants.